2017
DOI: 10.1007/s00705-017-3374-5
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of a novel virus, bellflower veinal mottle virus, suggests the existence of a new genus within the family Potyviridae

Abstract: A new virus was isolated from a bellflower (Campanula takesimana) plant showing veinal mottle symptoms, and its complete genome sequence was determined. The viral genome consists of a positive-sense single-stranded RNA of 8,259 ribonucleotides. Electron microscopic observation revealed that the viral genome is packaged as a filamentous particle with an average length of approximately 760 nm. BLAST searches of protein databases showed that the encoded polyprotein has a maximum amino acid sequence identity of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This element was necessary for the internal initiation function of the TriMV 5= UTR both in vitro and in vivo. Phylogenetic analysis of members of the Potyviridae family and functional comparisons between the TriMV 5= UTR and that of the Bellflower veinal mottle virus (BVMoV), a newly discovered potyvirus of bellflower (34), suggest a possible remnant motif among potyviruses. To our knowledge, this is the first evidence of a IRES-driven motif-based mechanism for translation conserved in both plant-and animal-hosted picornaviruses.…”
mentioning
confidence: 99%
“…This element was necessary for the internal initiation function of the TriMV 5= UTR both in vitro and in vivo. Phylogenetic analysis of members of the Potyviridae family and functional comparisons between the TriMV 5= UTR and that of the Bellflower veinal mottle virus (BVMoV), a newly discovered potyvirus of bellflower (34), suggest a possible remnant motif among potyviruses. To our knowledge, this is the first evidence of a IRES-driven motif-based mechanism for translation conserved in both plant-and animal-hosted picornaviruses.…”
mentioning
confidence: 99%
“…Although goji berry has been grown worldwide, viruses infecting goji berry are rather unknown. Thus, to identify the causal agent(s), the total RNA extracted from this sample was subjected to RNA-Seq as described previously [ 10 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…RNA-Seq was performed using an Illumina HiSeq2000 sequencer (Illumina, Inc., USA). De novo assembly of the quality filtered RNA-Seq reads was performed using the Trinity pipeline and assembled contigs were analyzed by BLASTn and BLASTx searches against the viral reference genome database in GenBank [ 10 , 16 ]. The entire RNA-Seq procedure was performed by Macrogen Inc. (Seoul, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…The other 11 genera each contain one to ten recognized species. The genus Bevemovirus has a single approved species, the Bellflower veinal mottle virus (BVMoV), which was isolated from a bellflower (Campanula takesimana) (Seo et al, 2017). The BVMoV polyprotein is predicted to be cleaved to produce nine mature proteins, HC-Pro, P3, 6K1, CI, 6K2, VPg, NIa-Pro, NIb, and CP; this is the same as that of macluravirus polyproteins.…”
Section: Introductionmentioning
confidence: 99%
“…The BVMoV polyprotein is predicted to be cleaved to produce nine mature proteins, HC-Pro, P3, 6K1, CI, 6K2, VPg, NIa-Pro, NIb, and CP; this is the same as that of macluravirus polyproteins. Phylogenetic analysis using BVMoV and selected potyvirid polyprotein sequences suggested that the genus Bevemovirus is the sister taxon of the genus Macluravirus (Seo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%